Efek Penyangga Modal Terhadap Transmisi Kebijakan Moneter Pada Kredit Perbankan Indonesia - Baharuddin, Baharuddin; Fungky Muchsidin, Feronica; A.We Tenri Fatimah Singkeruang; Nuraeni Saeni (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
This study aims to analyse the determinants and dynamics of Indonesian bank credit growth after the pandemic, focusing on monetary-policy transmission and the moderating role of capital buffer. Using an explanatory quantitative approach, quarterly panel data of 47 commercial banks (Q12020 – Q22025) were estimated with two-step System Generalized Method of Moments (System-GMM). Results show that credit growth exhibits negative dynamic persistence, capital buffer has a significant positive effect, while profitability and macroeconomic variables are insignificant. The central finding is a significantly negative interaction between capital buffer and the BI Rate, validating a capital-hoarding mechanism: well-capitalised banks restrain credit expansion when the policy rate rises. The results are robust to alternative specifications and instrument-validity tests. The study contributes a “Conditional Bank Lending” framework and recommends a dual-speed monetary transmission approach and a more responsive countercyclical capital buffer.